MINAT SISWA SEKOLAH MENENGAH ATAS TERHADAP LITERASI NUMERASI BERBASIS BUDAYA ACEH - Rohantizani, Rohantizani; Marhami, Marhami; Herizal, Herizal; Nuraina, Nuraina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research was initiated because of the change in the national examination assessment system (UN) to a Minimum Competency Assessment (AKM) and a Character Survey. In addition to students' ability to answer questions, it is also necessary to pay attention to student interests, especially their interest in AKM questions. The number of AKM questions faced by students cannot be separated from everyday life. Culture is something that is very often faced by students in their lives.This study aims to analyze students' interest in numeracy literacy questions based on Acehnese culture. The study used a descriptive qualitative type with the subject of 70 students of class X SMA. The data was obtained by distributing online questionnaires asking students with indicators of interest, namely feelings of pleasure, attention, interest, and student involvement in Acehnese culture-based numeracy AKM questions. The data were analyzed using the percentage technique. The results obtained are 62.96% for the first indicator (feeling happy), 70.62% for the second indicator (attention), 66.61% for the third indicator (interest), and 63.48% for the fourth indicator (involvement). From these results, it can be concluded that the tenth graders of SMA Negeri 1 Lhokseumawe have a good interest in Acehnese culture-based numeracy literacy assesment